Gardenia jasminoides: an ornamental plant for the biosorption of lead and cadmium ions. Issue 22 (8th May 2016) - Rafiq, Moniba; Farooq, Umar; Athar, M.; Salman, M.; Aslam, M.; Raza, H.M. Hamid
Abstract: The present study is about the removal of lead and cadmium ions by biodegradable powdered biomass from an ornamental plant Gardenia jasminoides (GJB). The characterization by Fourier transformed infrared showed that the biomass consists of amino, hydroxyl, carbonyl, and halide functional groups. The pHpzc and the concentration of acidic sites (10.5 mmol/g) and basic sites (7 mmol/g) were also determined. The effects of environmental parameters (varying initial Pb(II) and Cd(II) ions concentrations, time of contact, and pH) were studied. At contact times of 20 and 30 min, the sorption of Pb(II) and Cd(II) ions onto GJB was found to be maximum at pH 5 and 6, respectively. The pseudo-second-order kinetic model was followed by the biosorption of both metal ions. Non-linear equilibrium modeling showed that Langmuir model was suitable to describe the equilibrium with a q max for Pb(II) ions as 131.6 mg/g and for Cd(II) as 48.54 mg/g, respectively. Thus, the biomass can be used effectively for the removal of lead and cadmium ions from aqueous solutions.